Freirean thinking/action: clues to a decolonial epistemology that cements a counter-hegemonic Human Ecology (Práxis Educativa, 2021)
This study aimed to analyze the contributions of the Freirean thinking/action in the construction of a decolonial epistemology that orients a Latin-American Human Ecology of counter-hegemonic inclination. Through a literature review of the Freirean production and the Latin-American intellectuals of the Human Ecology, it was done the interlocution  of knowledge and perspectives, resulting to announce Paulo Freire as a classic in the genealogy of decolonial thinking  and in the reinforcing of a Human Ecology engaged with social, cognitive and environmental justice, signaling emancipatory processes coming from different fronts of struggle, in such a special historical time of rise of oppressions articulated by capitalism with patriarchy and colonialism.Keywords: Freirean thinking/action. Decolonial epistemologies. Human Ecology.